Effect of Seasonal Variation on Pollution Load of Water of Hokersar Wetland: a Case Study of Queen Wetland of Kashmir, J&K, India - Bano, Haleema; Rather, Rauoof Ahmad; Malik, Shaista; Bhat, Mohd Ashraf; Khan, Afzal Husain; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP]; Mir, Ikhlaq Ahmad (Springer Nature, 2022)
Hokersar wetland is vital for the endurance of migratory birds, but the topography of wetland has been severely altered during the last four decades. This wetland area has reduced from 1875.04 ha in 1969 to 1300 ha in 2008 due to several reasons, viz, encroachments and pollution. Keeping these facts in view, the present study was carried out to determine the impact of anthropogenic activities on the water quality of the wetland. Standard methods were used for analyzing various physico-chemical characteristics of water of a wetland. Among all the four sites, inlet sampling site was having the highest mean value of turbidity (2.06 NTU), water temperature (23.55 °C), electrical conductivity (0.233 dS/m), nitrate-nitrogen (0.046 mg/L), nitrite nitrogen (0.681 mg/L), ammoniacal nitrogen (0.210 mg/L), calcium (48.60 mg/L), phosphate (0.071 mg/L), and potassium (0.456 mg/L). The highest mean value (11.34 mg/L) of magnesium was recorded at the outlet, also having maximum pH (7.10). The lowest mean values of all physico-chemical characteristics of water were observed at the outlet site except for pH and Mg. The highest mean value was found for water temperature (27.25 °C), EC (0.228 dS/m, nitrate-nitrogen (0.485 mg/L), nitrite-nitrogen (0.035 mg/L), ammoniacal nitrogen (0.196 mg/L), Ca (58.08 mg/L), phosphate (0.047 mg/L), and K (0.480 mg/L) during summer season. A decreasing trend of trace metal concentration at different site in all seasons was observed in the following order: inlet (polluted) > center > Trapa abundance site > outlet. Similarly, COD and BOD values ranged from 69.69 to 115.89 mg/L and 56.08 to 95.05 mg/L in three different seasons, respectively. The wetland’s BOD level (95.05 mg/L) is too high, indicating high pollution level. The results of the present study have indicated that the pollutants and trace elements find their entry into the aquatic ecosystem and are a matter of great concern.
Keywords: Biological oxygen demand; Hokersar wetland; Trace metal; Water quality